The effect of the dimensions of the banking service scale in determining the level of quality of banking service - a study in a sample of banks operating in Basra Governorate - Orouba Rashid Ali, (Iraqi Journal for Administrative Sciences, 2025)
This study aims at improving the banking service quality through selecting the measures more accuracy and suitability , the study applied on a sample of banks working in Basra governorate with a sample of (4) banks ,(2) of them belong to general sector & the other (2) belong to privet sector. For the purpose of collecting data a sample of customers with (166) unit was chosen . The study reaches a group of results , the most important is the necessity of understanding the customer perceptions & evaluation for bank service , adding to that measuring service quality that presented to customer for the purpose of providing service with quality that satisfy the customer & attract to bank.